Effect of Nitrogen Rate and Application Interval on Yield and Profitability of Bilatidhonia - Mozumder, SN; Moniruzzaman, M; Sarker, PC (Journal of Agriculture & Rural Development, 2008)
The experiments on Bilatidhonia (Eryngium foetidum L.) crop comprising three levels of application interval (D1 = 15, D2 = 30 and D3 = 45 days after sowing) and four levels of nitrogen (N1 = 150, N2 = 175, N3 = 200 and N4 = 225 kg/ha) were carried out to determine the suitable N dose and application interval at ARS, Raikhali, Rangamati Hill District during two consecutive cropping season in 2003-04 and 2004-05. Plant height, number of leaves and leaf size had small variation with different nitrogen rates and application intervals. Number of plants/m2 and fresh yield singly or in combination differed significantly with different nitrogen rates and application intervals. The application of 175 kg-N/ha and 30 days interval gave the highest fresh yield (35.27 t/ha) and benefit cost ratio (3.61). Key words: Bilatidhonia, nitrogen rate, application interval, yield, profitability. doi:10.3329/jard.v6i1.1658 J Agric Rural Dev 6(1&2), 63-68, June 2008